Retailer corporate social responsibility and consumer citizenship behavior: The mediating roles of perceived consumer effectiveness and consumer trust. (July 2020) - Dang, Van Thac; Nguyen, Ninh; Pervan, Simon
Abstract: Retailers often face pressure from stakeholders to address social and environmental issues. The purpose of this study is to investigate the influence of retailer corporate social responsibility (CSR) on consumers' perceptions and behavior. Drawing on the theoretical foundations of social identity theory and signaling theory, this study presents and validates a unique model which examines the mediating effects of perceived consumer effectiveness and consumer trust on the relationship between retailer CSR and consumer citizenship behavior. Using a sample of 407 consumers in China, results of structural equation modeling show that retailer CSR is positively associated with consumer citizenship behavior. Additionally, perceived consumer effectiveness and consumer trust positively mediate this association. Taken together, these findings provide support for retailers to develop CSR programs that remind and reinforce consumers' perceptions about socially responsible behaviors.